Insight into the invasion process and immune-protective evaluation of Tp0971, a membrane lipoprotein from Treponema pallidum - Xiaohong Zhang; Junxia Duan; Yali Wang; Bibo Xie; Jie Zhou; Sisi Zhao; Weiguo Yin; Peng Liu; Feijun Zhao (Microbiology Spectrum, 2023)
ABSTRACT Treponema pallidum (T. pallidum), the pathogen of syphilis, can invade organisms through mucous membranes or broken skin and proliferate in the host. It spreads rapidly and causes chronic systemic multi-organ damage. Currently, the invasion and pathogenesis of T. pallidum remain a mystery. In this study, we established a T. pallidum infection model in New Zealand rabbits, and the T. pallidum burden in various tissues and organs was detected to investigate the dynamic spread of T. pallidum in different organs. Our results indicated that the T. pallidum burden in rabbits was in a cyclic and repeated dynamic process of decreasing and increasing after infection. In addition, the localization of lipoprotein Tp0971 was confirmed by using the gel microdroplet method. We found that Tp0971 might be a membrane lipoprotein that exists in the inner and outer membranes of T. pallidum. The immune-protective effect of the T. pallidum infection-dependent antigen Tp0971 was evaluated. Tp0971/CpG can induce high levels of Tp0971-specific antibodies, delay skin damage, and promote healing at the infected sites of T. pallidum in New Zealand rabbits. This indicated that Tp0971 may serve as a vaccine antigen candidate. Our results provide new ideas for future research on the proliferation, spread mechanism, and vaccine development of T. pallidum. IMPORTANCE The past two decades have seen a worldwide resurgence in infections caused by Treponema pallidum (T. pallidum) subsp. pallidum, the syphilis spirochete. The well-recognized capacity of the syphilis spirochete for early dissemination and immune evasion has earned it the designation “the stealth pathogen.” There are many hurdles to studying syphilis pathogenesis, most notably the difficulty of culturing and genetically manipulating T. pallidum, as well as the absence of an effective vaccine for T. pallidum prevention. T. pallidum infection in humans is a complex and lengthy process. In this study, we investigated the invasion process and the function of the infection-dependent antigen Tp0971 as an immunogen to inhibit the dissemination of T. pallidum in an animal infection model. This enables a better understanding of the specific pathogenic mechanism of this pathogen, syphilis pathogenesis, and vaccine research.